Perancangan Sistem Informasi Pencatatan Dan Pengarsipan Surat Masuk Serta Surat Keluar Di Dekanat Fakultas Teknik Universitas Sebelas Maret Surakarta - Sunarto Sunarto; Nuur Rochman Naafian; Kresno Ario Tri Wibowo (Indonesian Journal of Information Technology and Computing (IMAGING), 2022)
ABSTRACTÂ Correspondence activities are still needed and as proof of a valid document. The Faculty of Engineering, Universitas Sebelas Maret Surakarta (UNS) still uses letters to establish communication with outside parties. Good mail management will provide positive benefits for the agency. Considering the function of the letter which is quite important, it is better for the Faculty of Engineering, UNS, to ensure that the letter storage process can be carried out by following the agenda system procedure. Based on this background, the formulation of the problem to be solved in this research is "How to design an information system for incoming and outgoing letters at the Dean of the Faculty of Engineering UNS". The method used for the development of information systems is the System Development Life Cycle (SDLC) with the Waterfall model. The programming language used is PHP Native and MySQL database. The result of this research is the design of an information system for recording and filing letters that can be implemented at the Dean of the Faculty of Engineering, UNS. The design of this letter recording and archiving information system is expected to be used to manage letter data at the Dean of the Faculty of Engineering UNS properly following the agenda system procedure.Â